Optimisation of Self-Immolative Systems: Understanding the Role of the Reporter Group - Gavriel, Alexander (Cranfield University, 2019)
Stimuli-responsive materials have become significant targets in advance materials as systems of this type offer great potential to perform a variety of functions in a diverse range of applications that span drug delivery (1), biological and chemical sensors (2), diagnostics (3) and degradable polymers (4).Self-immolative (5) systems are comprised of a stable bond between trigger and reporter group, the stability of which is sensitive to particular agents and environments. Recently, we have described (6) the first examples of selective self-immolative systems triggered by a non-acidic electrophilic species to afford a facile colorimetric visual disclosure of toxic electrophilic alkylating agents. Through molecular design, we have carried out a systematic study on the reporter group to explore the balance between stability, reactivity and degradation of the self-immolative system. A structure-property relationship was established from the library of stimuli-responsive molecules synthesised, and an improved detector capable of disclosing electrophiles under ambient conditions realised.References: 1. M. Roth, O. Green, S. Gnaim and D. Shabat, Chemical Reviews, 2015, 116, 1309-1352.2. N. H. Ho, R. Weissleder and C. H. Tung, ChemBioChem, 2007, 8, 560.3. E. Sella and D. Shabat, J. Am. Chem. Soc., 2009, 131, 9934.4. A. Sagi, R. Weinstain, N. Karton and D. Shabat, J. Am. Chem. Soc., 2008, 130, 5434.5. C. A. Blencowe, A. T. Russell, F. Greco, W. Hayes and D. W. Thornthwaite, Polym. Chem., 2011, 2, 773.6. A. L. Acton, F. Leroux, A. Feula, K. Melia, M. R. Sambrook, W. Hayes and A. T. Russell, Chem. Commun., 2019, 55, 5219.
Keywords: 'Self-Immolative'; 'Colorimetric Disclosure'; 'Disclosure of Electrophilic Agents'; 'DSDS19 Poster'; 'DSDS19'; 'Chemical Engineering not elsewhere classified'